The Archaellum of Methanospirillum hungatei Is Electrically Conductive - David J. F. Walker (American Society for Microbiology, 2019)
ABSTRACT Microbially produced electrically conductive protein filaments are of interest because they can function as conduits for long-range biological electron transfer. They also show promise as sustainably produced electronic materials. Until now, microbially produced conductive protein filaments have been reported only for bacteria. We report here that the archaellum of Methanospirillum hungatei is electrically conductive. This is the first demonstration that electrically conductive protein filaments have evolved in Archaea. Furthermore, the structure of the M. hungatei archaellum was previously determined (N. Poweleit, P. Ge, H. N. Nguyen, R. R. O. Loo, et al., Nat Microbiol 2:16222, 2016, https://doi.org/10.1038/nmicrobiol.2016.222). Thus, the archaellum of M. hungatei is the first microbially produced electrically conductive protein filament for which a structure is known. We analyzed the previously published structure and identified a core of tightly packed phenylalanines that is one likely route for electron conductance. The availability of the M. hungatei archaellum structure is expected to substantially advance mechanistic evaluation of long-range electron transport in microbially produced electrically conductive filaments and to aid in the design of “green” electronic materials that can be microbially produced with renewable feedstocks. IMPORTANCE Microbially produced electrically conductive protein filaments are a revolutionary, sustainably produced, electronic material with broad potential applications. The design of new protein nanowires based on the known M. hungatei archaellum structure could be a major advance over the current empirical design of synthetic protein nanowires from electrically conductive bacterial pili. An understanding of the diversity of outer-surface protein structures capable of electron transfer is important for developing models for microbial electrical communication with other cells and minerals in natural anaerobic environments. Extracellular electron exchange is also essential in engineered environments such as bioelectrochemical devices and anaerobic digesters converting wastes to methane. The finding that the archaellum of M. hungatei is electrically conductive suggests that some archaea might be able to make long-range electrical connections with their external environment.